Meningkatkan Hasil Belajar Melalui Problem Based Learning (PBL) pada Materi Kemampuanku Terbatas VII SMP Negeri 2 Belimbing Hulu Kabupaten Melawi - Yupita Ngura; Timotius Tote Jelahu; Modestus Haryono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of class VII students of SMP Negeri 2 Belimbing Hulu 1 in the 2024/2025 academic year in the subject of Catholic Religious Education and Character Education through the application of the Problem Based Learning (PBL) learning model assisted by electronic media. This type of research is Classroom Action Research (CAR) which is carried out in two cycles with 2 meetings in each cycle. Each cycle consists of several stages, namely planning, implementing actions, observation and reflection. The first and second cycles discuss the material I have abilities and my abilities are limited. The subjects in this study were Catholic students of class VII of SMP Negeri 2 Belimbing Hulu in the 2024/2025 academic year consisting of 12 people. The main technique in data collection was carried out by means of tests and observations, while supporting techniques used interviews and documentation. The results of the study showed that the application of the Problem Based Learning (PBL) learning model assisted by YouTube Internet media can improve the learning outcomes of class VII students starting from cycle I and cycle II, namely 81 in cycle I increasing to 89 in cycle II. The conclusion of this study is that the application of the Problem Based Learning (PBL) learning model assisted by YouTube Internet media can improve the learning outcomes of Catholic Religious Education and Character Education of class VII students of SMP Negeri 2 Belimbing Hulu.